Pengaruh Model Pembelajaran Project Based Learning terhadap Hasil Belajar Mata Pelajaran Produk Kreatif dan Kewirausahaan Kelas XI SMK Negeri 1 Padang - Syaputra, Muhammad Marta; Efendi, Fiki; Prasetya, Febri; Rahim, Bulkia (Lembaga Yasin AlSys, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) learning model on student learning outcomes in Creative Products and Entrepreneurship subjects in class XI of SMK Negeri 1 Padang. The method used is quasi experiment with Nonequivalent Pretest-Posttest Control Group Design. The research sample consisted of two classes, namely the experimental class that applied the PjBL model and the control class that used conventional learning. The sampling technique used cluster random sampling with a total of 20 students per class. The instruments used included cognitive learning outcome tests and observation sheets for psychomotor aspects. The validity and reliability of the instruments were tested before use. Data were analyzed using normality, homogeneity, and t-test with the help of SPSS software. The results showed that there was a significant difference between student learning outcomes in the experimental and control classes. The average cognitive learning outcome of the experimental class was 80.25 while the control class was 70.25, with a percentage increase of 14.24%. Meanwhile, the average psychomotor score of the experimental class of 80.5 was higher than the control class of 74, with a percentage effect of 8.78%. Thus, the application of the Project Based Learning model proved effective in improving student learning outcomes, both in cognitive and psychomotor aspects. These findings support the importance of using innovative student-centered learning models to improve the quality of learning in vocational schools.